A taxonomic revision of the neotropical termite genus Diversitermes (Isoptera: Termitidae: Nasutitermitinae) - Oliveira, Danilo Elias; Constantino, Reginaldo (Zootaxa, 2016)
The taxonomy of the neotropical termite genus Diversitermes Holmgren 1912 is revised. Three species are recognized as valid: D. castaniceps (Holmgren 1910), D. diversimiles (Silvestri 1901) and D. tiapuan, sp. n. Identification keys based on soldiers and workers are presented. Diversitermes aporeticus Mathews 1977 is transferred to the genus Velocitermes Holmgren 1912. Diversitermes needhami Roonwal, Chhotani & Verma 1981 is a junior synonym of Velocitermes heteropterus (Silvestri 1901), and D. eidmanni Roonwal, Chhotani & Verma 1981 is a junior synonym of D. castaniceps (Holmgren 1910). Eutermes strelnicovi John 1920 (=Nasutitermes strelnicovi) is a junior synonym of D. diversimiles. All castes of the three valid species are described and illustrated. Distribution maps are presented for all species.